Periodicity of trunk growth in some Amazonian trees - Moraes, Vicente Haroldo F. (Pesquisa Agropecuaria Brasileira, 2014)
The trunk circumferences of 21 species were measured monthly with dendrometers in the Mocambo upland forest area. This is a reserve associated with the "Área de Pesquisas Ecológicas do Guamá" (Ecological experimental area of Guamá) of the Instituto de Pesquisas e Experimentação Agropecuárias do Norte (IPEAN), Belém, Pará, Brazil. The data, gathered from October 1966 through September 1967, showed a definite seasonal periodicity of trunk growth for 17 species. The fastest growth occurred during the rainy season. Additional information including the results of phenological studies, microclimatic data, and water balance studies will be necessary before the periodicity mechanism is understood.